LEADING ROLE OF KINEZOTHERAPY IN REHABILITATION OF PATIENTS AFTER OSTEOSYNTHESIS WITH APPLICATION OF MODERN CONSTRUCTIONS - A. N. Shimbaretskiy (Travmatologiâ i Ortopediâ Rossii, 2012)
Reliable fixation of bone splinters with the latest constructions increases the role of kinezotherapy in rehabilitation of the patients with fractures at all stages of treatment. The 50-years’ experience of surgical work in the Department of Traumatology and also regular examinations of patients at the out-patient department of the Institute persuade the author that knowing the basis of kinezotherapy is necessary for operating traumatologists who are the first to give recommendations for the patients marking the main stages and methods of functional therapy. The essential particularities and details of kinezotherapy after application of modern implants are revealed in the article. It is necessary to underline that exercises being maximally easy are very important and necessity of calculation of gravitational loading for the patients with the fractures of proximal parts of extremity is essential.